Metformin Use Is Associated With Lower Mortality in Veterans With Diabetes Hospitalized With Pneumonia. (28th December 2022) - Mohammed, Turab; Bowe, Michael; Plant, Alexandria; Perez, Mario; Alvarez, Carlos A; Mortensen, Eric M
Abstract: Background: Recent studies suggest that metformin use may be associated with improved infectious disease–related outcomes, whereas other papers suggest potentially worse outcomes in serious bacterial infections. Our purpose was to examine the association of prior outpatient prescription of metformin on 30- and 90-day mortality for older veterans with pre-existing diabetes hospitalized with pneumonia. Methods: We conducted a retrospective cohort study using national Department of Veterans Affairs data of patients ≥65 years with a prior history of diabetes who were hospitalized with pneumonia over a 10-year period (fiscal years 2002–2012.) For our primary analysis, we created a propensity score and matched metformin users to nonusers 1:1. Results: We identified 34 759 patients who met the inclusion criteria, 20.3% of whom were prescribed metformin. Unadjusted 30-day mortality was 9.6% for those who received metformin versus 13.9% in nonusers ( P < .003), and 90-day mortality was 15.8% for those who received metformin versus 23.0% for nonusers ( P < .0001). For the propensity score model, we matched 6899 metformin users to 6899 nonusers. After propensity matching, both 30-day (relative risk [RR]: .86; 95% confidence interval [CI]: .78–.95) and 90-day (RR: .85; 95% CI: .79–.92) mortality was significantly lower for metformin users. Conclusions: Prior receipt of metformin was associated with significantly lower mortality after adjusting for potential confounders. Additional research is needed to examine the safety and potential benefits of metformin use in patients with respiratory infections. Abstract : Patients with diabetes are at higher risk for serious infections and worse outcomes. We found that, for veterans with diabetes who were hospitalized with pneumonia, prior metformin use was associated with improved short-term survival.